Monad's associativity rule in haskell - haskell

(m >>= f) >>= g = m >>= (\x -> f x >>= g)
what's different from f and \x->f x ??
I think they're the same type a -> m b. but it seems that the second >>= at right side of equation treats the type of \x->f x as m b.
what's going wrong?

The expressions f and \x -> f x do, for most purposes, mean the same thing. However, the scope of a lambda expression extends as far to the right as possible, i.e. m >>= (\x -> (f x >>= g)).
If the types are m :: m a, f :: a -> m b, and g :: b -> m c, then on the left we have (m >>= f) :: m b, and on the right we have (\x -> f x >>= g) :: a -> m c.
So, the difference between the two expressions is just which order the (>>=) operations are performed, much like the expressions 1 + (2 + 3) and (1 + 2) + 3 differ only in the order in which the additions are performed.
The monad laws require that, like addition, the answer should be the same for both.

Related

Haskell - applying a function that returns a functor onto a functor

Say I have function two functions f and g that both take in regular values and return an Either value like so:
g :: a -> Either x b
f :: b -> Either x c
How do I chain the two together to get something like f . g?
The best solution I have come up with is creating a helper function called applyToRight that works like this
applyToRight :: (a -> Either x b) -> Either x a -> Either x b
applyToRight f x =
case x of
Left a -> Left a
Right b -> f b
So that I can then do
applyToRight f (g a)
In this case I am specifically talking about Either, but I think this problem could be generalized to all applicative functors. What is the most elegant way to deal with this?
Not Applicative. You have rediscovered the Monadic bind:
(>>=) :: Monad m => m a -> (a -> m b) -> m b
Either x is a Monad:
> Left "a" >>= (\x -> Right (1+x))
Left "a"
> Right 1 >>= (\x -> Right (1+x))
Right 2
Chaining two monad-creating functions like you have is done with the Kleisli composition operator, like f <=< g, or equivalently in the other direction g >=> f with the forward composition operator,
(>=>) :: Monad m => (a -> m b) -> (b -> m c) -> a -> m c
the types are easier to follow with this one:
f :: b -> Either x c
g :: a -> Either x b
-----------------------------------------
g >=> f :: a -> Either x c
In fact one way to summarize the monads is to say they are about the generalized function composition.
>=> is defined simply as
(g >=> f) x = g x >>= f
(f <=< g) x = g x >>= f = f =<< g x
See also:
Monadic types diagram
Generalized function application
More links here
Functor and Applicative are both too weak: Monad contains the function you seek.
applyToRight = flip (>>=)

How does <*> derived from pure and (>>=)?

class Applicative f => Monad f where
return :: a -> f a
(>>=) :: f a -> (a -> f b) -> f b
(<*>) can be derived from pure and (>>=):
fs <*> as =
fs >>= (\f -> as >>= (\a -> pure (f a)))
For the line
fs >>= (\f -> as >>= (\a -> pure (f a)))
I am confused by the usage of >>=. I think it takes a functor f a and a function, then return another functor f b. But in this expression, I feel lost.
Lets start with the type we're implementing:
(<*>) :: Monad f => f (a -> b) -> f a -> f b
(The normal type of <*> of course has an Applicative constraint, but here we're trying to use Monad to implement Applicative)
So in fs <*> as = _, fs is an "f of functions" (f (a -> b)), and as is an "f of as".
We'll start by binding fs:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= _
If you actually compile that, GHC will tell us what type the hole (_) has:
foo.hs:4:12: warning: [-Wtyped-holes]
• Found hole: _ :: (a -> b) -> f b
Where: ‘a’, ‘f’, ‘b’ are rigid type variables bound by
the type signature for:
(Main.<*>) :: forall (f :: * -> *) a b.
Monad f =>
f (a -> b) -> f a -> f b
at foo.hs:2:1-45
That makes sense. Monad's >>= takes an f a on the left and a function a -> f b on the right, so by binding an f (a -> b) on the left the function on the right gets to receive an (a -> b) function "extracted" from fs. And provided we can write a function that can use that to return an f b, then the whole bind expression will return the f b we need to meet the type signature for <*>.
So it'll look like:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= (\f -> _)
What can we do there? We've got f :: a -> b, and we've still got as :: f a, and we need to make an f b. If you're used to Functor that's obvious; just fmap f as. Monad implies Functor, so this does in fact work:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= (\f -> fmap f as)
It's also, I think, a much easier way to understand the way Applicative can be implemented generically using the facilities from Monad.
So why is your example written using another >>= and pure instead of just fmap? It's kind of harkening back to the days when Monad did not have Applicative and Functor as superclasses. Monad always "morally" implied both of these (since you can implement Applicative and Functor using only the features of Monad), but Haskell didn't always require there to be these instances, which leads to books, tutorials, blog posts, etc explaining how to implement these using only Monad. The example line given is simply inlining the definition of fmap in terms of >>= and pure (return)1.
I'll continue to unpack as if we didn't have fmap, so that it leads to the version you're confused by.
If we're not going to use fmap to combine f :: a -> b and as :: f a, then we'll need to bind as so that we have an expression of type a to apply f to:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= (\f -> as >>= (\a -> _))
Inside that hole we need to make an f b, and we have f :: a -> b and a :: a. f a gives us a b, so we'll need to call pure to turn that into an f b:
(<*>) :: Monad f => f ( a -> b) -> f a -> f b
fs <*> as
= fs >>= (\f -> as >>= (\a -> pure (f a)))
So that's what this line is doing.
Binding fs :: f (a -> b) to get access to an f :: a -> b
Inside the function that has access to f it's binding as to get access to a :: a
Inside the function that has access to a (which is still inside the function that has access to f as well), call f a to make a b, and call pure on the result to make it an f b
1 You can implement fmap using >>= and pure as fmap f xs = xs >>= (\x -> pure (f x)), which is also fmap f xs = xs >>= pure . f. Hopefully you can see that the inner bind of your example is simply inlining the first version.
Applicative is a Functor. Monad is also a Functor. We can see the "Functorial" values as standing for computations of their "contained" ⁄ produced pure values (like IO a, Maybe a, [] a, etc.), as being the allegories of ⁄ metaphors for the various kinds of computations.
Functors describe ⁄ denote notions ⁄ types of computations, and Functorial values are reified computations which are "run" ⁄ interpreted in a separate step which is thus akin to that famous additional indirection step by adding which, allegedly, any computational problem can be solved.
Both fs and as are your Functorial values, and bind ((>>=), or in do notation <-) "gets" the carried values "in" the functor. Bind though belongs to Monad.
What we can implement in Monad with (using return as just a synonym for pure)
do { f <- fs ; -- fs >>= ( \ f -> -- fs :: F (a -> b) -- f :: a -> b
a <- as ; -- as >>= ( \ a -> -- as :: F a -- a :: a
return (f a) -- return (f a) ) ) -- f a :: b
} -- :: F b
( or, with MonadComprehensions,
[ f a | f <- fs, a <- as ]
), we get from the Applicative's <*> which expresses the same computation combination, but without the full power of Monad. The difference is, with Applicative as is not dependent on the value f there, "produced by" the computation denoted by fs. Monadic Functors allow such dependency, with
[ bar x y | x <- xs, y <- foo x ]
but Applicative Functors forbid it.
With Applicative all the "computations" (like fs or as) must be known "in advance"; with Monad they can be calculated -- purely -- based on the results of the previous "computation steps" (like foo x is doing: for (each) value x that the computation xs will produce, new computation foo x will be (purely) calculated, the computation that will produce (some) y(s) in its turn).
If you want to see how the types are aligned in the >>= expressions, here's your expression with its subexpressions named, so they can be annotated with their types,
exp = fs >>= g -- fs >>=
where g f = xs >>= h -- (\ f -> xs >>=
where h x = return (f x) -- ( \ x -> pure (f x) ) )
x :: a
f :: a -> b
f x :: b
return (f x) :: F b
h :: a -> F b -- (>>=) :: F a -> (a -> F b) -> F b
xs :: F a -- xs h
-- <-----
xs >>= h :: F b
g f :: F b
g :: (a -> b) -> F b -- (>>=) :: F (a->b) -> ((a->b) -> F b) -> F b
fs :: F (a -> b) -- fs g
-- <----------
fs >>= g :: F b
exp :: F b
and the types of the two (>>=) applications fit:
(fs :: F (a -> b)) >>= (g :: (a -> b) -> F b)) :: F b
(xs :: F a ) >>= (h :: (a -> F b)) :: F b
Thus, the overall type is indeed
foo :: F (a -> b) -> F a -> F b
foo fs xs = fs >>= g -- foo = (<*>)
where g f = xs >>= h
where h x = return (f x)
In the end, we can see monadic bind as an implementation of do, and treat the do notation
do {
abstractly, axiomatically, as consisting of the lines of the form
a <- F a ;
b <- F b ;
......
n <- F n ;
return (foo a b .... n)
}
(with a, F b, etc. denoting values of the corresponding types), such that it describes the overall combined computation of the type F t, where foo :: a -> b -> ... -> n -> t. And when none of the <-'s right-hand side's expressions is dependent on no preceding left-hand side's variable, it's not essentially Monadic, but just an Applicative computation that this do block is describing.
Because of the Monad laws it is enough to define the meaning of do blocks with just two <- lines. For Functors, just one <- line is allowed ( fmap f xs = do { x <- xs; return (f x) }).
Thus, Functors/Applicative Functors/Monads are EDSLs, embedded domain-specific languages, because the computation-descriptions are themselves values of our language (those to the right of the arrows in do notation).
Lastly, a types mandala for you:
T a
T (a -> b)
(a -> T b)
-------------------
T (T b)
-------------------
T b
This contains three in one:
F a A a M a
a -> b A (a -> b) a -> M b
-------------- -------------- -----------------
F b A b M b
You can define (<*>) in terms of (>>=) and return because all monads are applicative functors. You can read more about this in the Functor-Applicative-Monad Proposal. In particular, pure = return and (<*>) = ap is the shortest way to achieve an Applicative definition given an existing Monad definition.
See the type signatures for (<*>), ap and (>>=):
(<*>) :: Applicative f => f (a -> b) -> f a -> f b
ap :: Monad m => m (a -> b) -> m a -> m b
(>>=) :: Monad m => m a -> (a -> m b) -> m b
The type signature for (<*>) and ap are nearly equivalent. Since ap is written using do-notation, it is equivalent to some use of (>>=). I'm not sure this helps, but I find the definition of ap readable. Here's a rewrite:
ap m1 m2 = do { x1 <- m1; x2 <- m2; return (x1 x2) }
≡ ap m1 m2 = do
x1 <- m1
x2 <- m2
return (x1 x2)
≡ ap m1 m2 =
m1 >>= \x1 ->
m2 >>= \x2 ->
return (x1 x2)
≡ ap m1 m2 = m1 >>= \x1 -> m2 >>= \x2 -> return (x1 x2)
≡ ap mf ma = mf >>= (\f -> ma >>= (\a -> pure (f a)))
Which is your definition. You could show that this definition upholds the applicative functor laws, since not everything defined in terms of (>>=) and return does that.

How are monoid and applicative connected?

I am reading in the haskellbook about applicative and trying to understand it.
In the book, the author mentioned:
So, with Applicative, we have a Monoid for our structure and function
application for our values!
How is monoid connected to applicative?
Remark: I don't own the book (yet), and IIRC, at least one of the authors is active on SO and should be able to answer this question. That being said, the idea behind a monoid (or rather a semigroup) is that you have a way to create another object from two objects in that monoid1:
mappend :: Monoid m => m -> m -> m
So how is Applicative a monoid? Well, it's a monoid in terms of its structure, as your quote says. That is, we start with an f something, continue with f anotherthing, and we get, you've guessed it a f resulthing:
amappend :: f (a -> b) -> f a -> f b
Before we continue, for a short, a very short time, let's forget that f has kind * -> *. What do we end up with?
amappend :: f -> f -> f
That's the "monodial structure" part. And that's the difference between Applicative and Functor in Haskell, since with Functor we don't have that property:
fmap :: (a -> b) -> f a -> f b
-- ^
-- no f here
That's also the reason we get into trouble if we try to use (+) or other functions with fmap only: after a single fmap we're stuck, unless we can somehow apply our new function in that new structure. Which brings us to the second part of your question:
So, with Applicative, we have [...] function application for our values!
Function application is ($). And if we have a look at <*>, we can immediately see that they are similar:
($) :: (a -> b) -> a -> b
(<*>) :: f (a -> b) -> f a -> f b
If we forget the f in (<*>), we just end up with ($). So (<*>) is just function application in the context of our structure:
increase :: Int -> Int
increase x = x + 1
five :: Int
five = 5
increaseA :: Applicative f => f (Int -> Int)
increaseA = pure increase
fiveA :: Applicative f => f Int
fiveA = pure 5
normalIncrease = increase $ five
applicativeIncrease = increaseA <*> fiveA
And that's, I guessed, what the author meant with "function application". We suddenly can take those functions that are hidden away in our structure and apply them on other values in our structure. And due to the monodial nature, we stay in that structure.
That being said, I personally would never call that monodial, since <*> does not operate on two arguments of the same type, and an applicative is missing the empty element.
1 For a real semigroup/monoid that operation should be associative, but that's not important here
Although this question got a great answer long ago, I would like to add a bit.
Take a look at the following class:
class Functor f => Monoidal f where
unit :: f ()
(**) :: f a -> f b -> f (a, b)
Before explaining why we need some Monoidal class for a question about Applicatives, let us first take a look at its laws, abiding by which gives us a monoid:
f a (x) is isomorphic to f ((), a) (unit ** x), which gives us the left identity. (** unit) :: f a -> f ((), a), fmap snd :: f ((), a) -> f a.
f a (x) is also isomorphic f (a, ()) (x ** unit), which gives us the right identity. (unit **) :: f a -> f (a, ()), fmap fst :: f (a, ()) -> f a.
f ((a, b), c) ((x ** y) ** z) is isomorphic to f (a, (b, c)) (x ** (y ** z)), which gives us the associativity. fmap assoc :: f ((a, b), c) -> f (a, (b, c)), fmap assoc' :: f (a, (b, c)) -> f ((a, b), c).
As you might have guessed, one can write down Applicative's methods with Monoidal's and the other way around:
unit = pure ()
f ** g = (,) <$> f <*> g = liftA2 (,) f g
pure x = const x <$> unit
f <*> g = uncurry id <$> (f ** g)
liftA2 f x y = uncurry f <$> (x ** y)
Moreover, one can prove that Monoidal and Applicative laws are telling us the same thing. I asked a question about this a while ago.

Applicative scanning arguments right to left

I have come across several situations where I would like to use applicative style f <$> x1 <*> x2 <*> x3 but scanning the applicative arguments right to left instead of the usual left to right.
Naturally, if I bring this into a monadic context, I can do this without problem:
liftM3' :: Monad m => (a1 -> a2 -> a3 -> r) -> m a1 -> m a2 -> m a3 -> m r
liftM3' f x1 x2 x3 = do { x3' <- x3; x2' <- x2; x1' <- x1; return f x1' x2' x3' }
So, for my question: is there some general method to accomplish this in the context of only Applicative (perhaps a newtype wrapper) and if not, why can there not be one. That said, any insight about elegant solutions or workarounds to this problem are welcome.
Aside: My solution had been to define new right associative operators, but the solution was by no means elegant.
Edit: Here is my solution (I'd be interested in knowing if there is something equivalent in the standard libraries), if I require Monad:
newtype Reverse m a = Reverse (m a)
instance Monad m => Functor (Reverse m) where
f `fmap` x = pure f <*> x
instance Monad m => Applicative (Reverse m) where
pure x = Reverse $ return x
(Reverse f) <*> (Reverse x) = Reverse $ do { x' <- x; f' <- f; return $ f' x' }
The Backwards type is like your Reverse, and in a semi-standard package.
Naturally, if I bring this into a monadic context, I can do this without problem:
Don't forget that f is just a function. As such, you can simply define another function that takes the arguments in another order and then fall back to the usual applicative combinators:
-- | Lifts the given function into an applicative context.
-- The applicative effects are handled from right-to-left
-- e.g.
-- >>> liftA3 (\_ _ _ -> ()) (putStr "a") (putStr "b") (putStr "c")
-- will put "cba" on your console.
liftA3Rev :: Applicative f => (a -> b -> c -> d) -> f a -> f b -> f c -> f d
liftA3Rev f x y z = f' <$> z <*> y <*> x
where
f' = \c b a -> f a b c
It's probably either impossible, or quite hard to write this with operators only, though. This is due to the nature of partial application. Remember that for f :: Int -> Char -> Bool and Applicative f => f Int, the expression f <$> x
has type Applicative f => f (Char -> Bool). We always "lose" types on the left end, not on the right end. If you change the order of arguments, it's easy again:
(>*>) :: Applicative f => f a -> f (a -> b) -> f b
(>*>) = flip (<*>)
infixr 4 >*> -- right associative
liftA3Rev' :: Applicative f => (a -> b -> c -> d) -> f a -> f b -> f c -> f d
liftA3Rev' f x y z = z >*> y >*> x >*> pure f

Help in understanding pointfree code

When playing around with Pointfree I was presented with a piece of code that I can't seem to understand.
:pl map (\x -> x * x) [1..10]
-- map (join (*)) [1..10]
My main problem is that I don't get how join works here. I understand that it 'removes' one layer of a monadic wrapping (m (m a) to m a). I figure it boils down to something like [1..10] >>= (\x -> [x * x]), but I don't really get how the "extra layer" gets introduced. I get that join x = x >>= id, but then I'm still stuck on how that "duplicates" each value so that (*) gets two arguments. This has been bugging me for about half an hour now and I'm mostly annoyed at myself, because I feel like I have all the puzzle pieces but can't seem to fit them together...
P.S. Don't worry, I would't really use this pointfree version, this is pure curiosity and an attempt to understand Haskell better.
join is using the instance of Monad for (->) a, as defined in Control.Monad.Instances. The instance is similar to Reader, but without an explicit wrapper. It is defined like this:
instance Monad ((->) a) where
-- return :: b -> (a -> b)
return = const
-- (>>=) :: (a -> b) -> (b -> a -> c) -> (a -> c)
f >>= g = \x -> g (f x) x
If you now reduce join using this instance:
join
(>>= id)
flip (\f g x -> g (f x) x) (\a -> a)
(\f x -> (\a -> a) (f x) x)
(\f x -> f x x)
As you can see, the instance for (->) a makes join to a function that applies an argument twice. Because of this, join (*) is simply \x -> x * x.

Resources